PENYULUHAN PENGHEMATAN ENERGI LISTRIK PADA RUMAH TANGGA - Simon Patabang; Jeremias M. Leda; Limbran Sampebatu; Syaban Ramadhan; Chasper Steven More (Gapenas Publisher, 2023)
Extension activities were carried out in the Karanganyar Village area, Kec. Mamajang, Makassar. In general, partners have houses that are close to each other or attached to neighbors so that the air circulation in the house is not good and the natural lighting in the house is not optimal. To get optimal lighting during the day, you must use electric lights as a source of lighting. Then to get fresh and comfortable air, partners use air conditioners or fans. With such a situation, partners experience difficulties with the cost of electricity bills which tend to increase every month. The partner's problem is how to reduce the cost of electricity bills which tend to increase every month. To help overcome partner problems, counseling on saving electricity is carried out. The main ingredients of energy-saving counseling are introducing energy-efficient electrical devices, building awareness of the importance of saving energy, and how to calculate the cost of a monthly electricity bill in one household. Based on the results of the implementation and evaluation of energy saving counseling and the results of observations, partners have realized how important it is to save energy. The cost of electricity bills from several partners has decreased compared to the previous period. This counseling has increased partners' knowledge so that they understand more about the positive and negative impacts of regular and disciplined use of electric power in the household